Music for the temple of Lima’s San Agustin convent. The Chapelmaster Fray Cipriano Aguilar - Vega Zavala, César Humberto (2023)
Cipriano Aguilar Fernández was an Augustinian friar whose life took place during the transition from viceregal to republican Peru. In 1837 he was named chapel master of the Augustinian convent of Lima. Some of his works have been founded but none of them in said Lima convent. These works present evidence that Cipriano Aguilar assimilated the musical style of Joseph Haydn, but subject to the way in which said aesthetic was implemented in Spain, during the last 20 years of the 18th century, in which the orchestra was used as accompaniment for liturgical vocal music. In this context, the convent space became a center for training of Lima musicians, singers and instrumentalists. Likewise, the aesthetic development of a musical practice is observed that survived until 20 years after Independence from Spain and allows us to infer that we broke politically with the Iberian nation but, we tried to maintain relationships with European´s culture.